Komposisi Musik Tradisi Dengan Media Trebang: Pendampingan Musik Trebang di Banyuwangi - maskur, Mochamad (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2024)
Trebang is the name for the tambourine musical instrument which can be found in the daily conversation of theBanyuwangi people. Trebang means to fly, the meaning of this word can be seen through the rhythm of the trebangangebyar kerokan strikes which are carried out with extra energy and balanced with a high playing spirit or in the Usinglanguage it is called oyak-oyakan with a fast rhythm that occurs spontaneously, so this can deceive the senses. playersget tired until they feel like they are floating without reducing the value of the characteristics of the game. There areso many types of trebang that they have different names, including trebang ketimpring, marawis, biang, salun,gembrung, and trebang Banyuwangi or others, each trebang has its own characteristics both in terms of shape, soundcolor and playing technique. In the Banyuwangi trebangan game which is usually played by artists, it has three basicsounds including (prang, bring, teng) or can be written using the letter notation method (p-b-t) according to the colorof the trebang sound itself with the artist's language intended to facilitate learning and maintain values. -Traditionalvalues that apply without having to imitate other languages which can obscure the indigenous language, especiallythe Banyuwangi language, with the principle of respecting and loving the culture of the Indonesian nation, especiallythe culture of the local people, namely Banyuwangi. By combining these three basic sounds with the inclusion of thestroke pattern, various trebangan timpal stroke styles are created, such as trebangan jos, trebangan yahum, trebangantimim, trebangan gebyar, and trebangan melaku. Five of these trebangan styles can be developed according to theirneeds, namely depending on the artist's creativity, so that each existing trebang group has a variety of trebanganstrokes with different names or usually uses its own language such as trebangan jos siji and jos loro, trebangan yahumsiji, yahum loro, yahum telu , and yahum papat, trebangan tiram wavean, tiram pencakan, and tiram kembangan,trebangan gebyar krotokan, gebyar grudhugan, gebyar kentrogan and gebyar kluthikan, while trebangan melakuincludes trebangan melaku plain and melaku pinjalan.